Perception of the value of generic drugs in São Paulo, Brazil - Elene Paltrinieri Nardi; Marcos Bosi Ferraz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2016)
Abstract The objective of this study was to assess the perceptions of opinion-leaders, patients and their accompanying family members or carers about generic drugs. Three groups of participants were surveyed: (i) 50 customers while they were visiting commercial pharmacies located in São Paulo city, Brazil, (ii) 25 patients and 25 companions while they were waiting at the university outpatient clinic, and (iii) 50 healthcare opinion-leaders from government, hospitals, health plans, academia, and pharmaceutical companies. The questions explored socio-demographic characteristics and perceptions regarding value attributes of generic drugs compared to brand name drugs. Respondents had an average age of 52 years and 53% were women. Respondents believed generic drugs to be cheaper than brand name drugs (97%), and 31% thought generic drugs to be less effective than brand name drugs. Also, generic drugs were perceived by 54% of respondents to be as safe as brand name drugs and 74% would prefer brand name drugs if there was no price difference. In conclusion, multiple factors may contribute to the decision to buy generic drugs; among these, perceived effectiveness, safety and price appear to be the most important factors.